Investigation of TXNIP, VDR and hOGG1 gene expression patterns and potential therapeutic targets in bladder cancer patients: TXNIP, VDR, hOGG1 genes in bladder cancer - Acar, Esra; Dillioglugil, Meltem Ozlen; Sarihan, Mehmet; Yilmaz, Hasan; Yuksekkaya, Mustafa; Ates, Fatma; Ercan, Alev Meltem; Dillioglugil, Ozdal (Journal of Medical Science, 2024)
Backround. The aim of this study was to examine the expression levels of the Thioredoxin interacting protein (TXNIP), Vitamin D receptor (VDR), Human 8-oxoguanine DNA N-glycosylase 1 (hOGG1) genes in bladder cancer patients, according to clinical staging and determine the levels of potential therapeutic targets in serum samples.Material and Methods. Tissue and serum samples of patients who underwent transurethral resection (TUR) between 2017 and 2018 were obtained. Levels of TXNIP, hOGG1, and VDR genes were assessed using Real time-polymerase chain reaction (RT-PCR), while levels of Thioredoxin (Trx), 8-hydroxy-2' -deoxyguanosine (8-OHdG), and 1,25-dihydroxyvitamin D (25(OH)D3) were evaluated using the enzyme-linked immunosorbant assay (ELISA) method. Selenium levels were also measured using Optical Emission Spectroscopy (ICP-OES) in both tissue and serum samples. The protein-protein interactions and molecular and biological function of the proteins were assessed using Search Tool for the Retrieval of Interacting Genes/Proteins. Statistical analysis was conducted using IBM SPSS Statistics version 20.0.Results. The TXNIP gene showed higher expression in low-grade bladder cancer patients up to stage T1, but decreased in high-grade T1 and T2 stages. Both VDR and hOGG1 gene expressions were consistently lower across all clinical subgroups. No significant differences were found in serum 25(OH)D3, 8-OHdG, Hypoxia Inducible Factor 1 Alpha (HIF-1α), selenium (Se), and tissue Se levels.Conclusions. TXNIP mRNA expression was remarkably lower in advanced stages. VDR and hOGG1 expression were low in all bladder cancer subgroups. These parameters could serve as potential targets for preventing or treating bladder cancer.